2018
DOI: 10.1101/308775
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

KCH kinesin drives nuclear transport and cytoskeletal coalescence for tip cell growth

Abstract: Long-distance transport along microtubules (MTs) is critical for intracellular organisation. In animals, antagonistic motor proteins kinesin (plus end-directed) and dynein (minus end-directed) drive cargo transport. In land plants, however, the identity of motors responsible for transport is poorly understood, as genes encoding cytoplasmic dynein are missing. How other functions of dynein are brought about in plants also remains unknown. Here, we show that a subclass of the kinesin-14 family, KCH-which can als… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
3
4
0
Order By: Relevance
“…7c,d; Tables S5, S6). Notably Cellular Compartments of ‘kinesin complex’ (GO: 0005871) and ‘microtubule associated complex’ (GO: 0005875) that facilitated tip growth in P. patens were also enriched (Hiwatashi et al ., 2014; Yamada & Goshima, 2018), supporting our claim that PpRALF1 and PpRALF2 are involved in tip growth.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…7c,d; Tables S5, S6). Notably Cellular Compartments of ‘kinesin complex’ (GO: 0005871) and ‘microtubule associated complex’ (GO: 0005875) that facilitated tip growth in P. patens were also enriched (Hiwatashi et al ., 2014; Yamada & Goshima, 2018), supporting our claim that PpRALF1 and PpRALF2 are involved in tip growth.…”
Section: Resultssupporting
confidence: 85%
“…7c,d; Tables S5, S6). Notably Cellular Compartments of 'kinesin complex' (GO: 0005871) and 'microtubule associated complex' (GO: 0005875) that facilitated tip growth in P. patens were also enriched (Hiwatashi et al, 2014;Yamada & Goshima, 2018), supporting our claim that PpRALF1 and PpRALF2 are involved in tip growth. While a range of biological process GO terms in biosynthesis and metabolic turnover processes were enriched in both PpRALFs, we detected distinct Molecular Function GO terms between PpRALF1 and PpRALF2.…”
Section: Ppralf1 and Ppralf2 Regulate Distinct But Overlapping Genes ...supporting
confidence: 72%
“…MF and MT are able to respond to abiotic stress and AtKCH3 was involved in the regulation of abiotic stress response by regulating the dynamic changes of MF and MT. KCH transports nucleation and MT-actin interactions in flowering plants [56]. The results of low-speed coprecipitation showed that CH domain of AtKCH3 and AtKCH4 could promote MF bunching in vitro [57].…”
Section: Kchmentioning
confidence: 99%
“…In this system, when plus-end-directed motility is predominant over minus-end-directed motility, the organelle moves apically and is abundant on the apical side, and vice versa. Based on this advantage, several kinesin-14 family members have been identified as the drivers of retrograde transport, namely KCH for the nucleus, KCBP for the chloroplast and telophase chromosome, and ATK for newly formed microtubules [24][25][26] . Studies in P. patens thus drew a functional analogy between kinesin-14s and dynein and further illustrated the contribution of intracellular transport driven by the microtubule-kinesin mechanism.…”
Section: Introductionmentioning
confidence: 99%